Optimizing entropy production in bi-diffusive convection within trapezoidal Porous enclosure using radiative trihybrid nanofluids and T-shaped baffle - Hansda, Samrat; Chattopadhyay, Anirban; Goswami, Krishno D.; Pandit, Swapan K.; Oeztop, Hakan F.; Sheremet, Mikhail A. (Elsevier, 2025)
This study explores entropy production optimization and thermosolutal transfer enhancement in trapezoidal porous enclosure, commonly used in solar energy systems, electronic cooling, and chemical reactors. The objective is to evaluate the effects of radiative trihybrid nanoliquids on heat and mass transfer in a trapezoidal porous cavity filled with aluminum oxide, copper oxide, and silver nanoparticles dispersed in water, featuring a centrally located T-shaped cold baffle. The lower boundary of the cavity is uniformly heated and soluted, the side boundaries are cooled with low solute concentrations, and the upper boundary is insulated. The governing equations are solved using a Higher Order Compact (HOC) numerical scheme, focusing on parameters such as the Rayleigh number, radiation parameter, buoyancy ratio, and nanoparticle concentration. Results indicate that increasing the Rayleigh number from 104 to 106 significantly enhances heat and mass transfer rates. Average Nusselt and Sherwood numbers are increased up to 53.04% and 252.49%, respectively, across different configurations. Additionally, raising the radiation parameter values from 1 to 5 boosts the average Nusselt number up to 197.09%, highlighting the dominance of radiative thermal transport. The T-shaped baffle significantly influences flow patterns, reduces entropy generation, and optimizes thermal and solutal transport.
Keywords: Entropy production; Trihybrid nanofluid; T-shaped baffle; Thermal radiation; Trapezoidal cavity